Geothermal potential analysis using 3d modeling of subsurface structures based on the Gravity Anomaly in the Mount Lawu area, Central Java - Puspita Sari, Feby; Restiana, Andini; Firya Wardhianty, Nabila (Journal of Natural Sciences and Mathematics Research, 2023)
Over time, energy needs will continue to increase. Dependence on the use of fossil energy results in the availability of such energy will run out at any time, so it is necessary to develop research on geothermal energy that is environmentally friendly and renewable. One of the Geothermal Work areas is on Mount Lawu, located at coordinates between 111°15' east longitude and 7°30' south latitude in several districts Central Java Province and East Java Province. The purpose of this study is to provide information related to geothermal potential using the gravity method by knowing the temperature of the area and the 3D modeling of subsurface structures. Based on the results of the Second Vertical Derivative (SVD) analysis, three normal faults were found in geothermal sources. The modeling results show that the residual anomaly map depicts a distribution of high anomalies ranging between 2 mGal up to 6.5 mGal scattered from North to South and East to West, suspected to be caused by lava rock intrusion. The results of the 3D inversion model show there are three layers, namely clay rock, which is suspected to be cap rock at a depth of 500 - 2500 m, pyroclastic lava rock, which is suspected to be as a reservoir at a depth of 3000 - 4500 m, and lava, which is suspected to be as a reservoir heat source at a depth of 5000 - 8000 m. Based on the map in Land Surface Temperature (LST) obtained the temperature value of Mount Lawu ranging from 3.14 °C - to 23.25 °C.